1975
DOI: 10.1128/aem.29.4.537-539.1975
|View full text |Cite
|
Sign up to set email alerts
|

Violet Red Bile 2 Agar for Stressed Coliforms1

Abstract: Counts on a new, autoclave-sterilizable violet red bile (VRB-2) agar were compared with counts on freshly boiled VRB agar. Yields on VRB-2 agar averaged 217, 180, 130, and 112% of counts obtained on the control medium for samples of water, cottage cheese, frozen vegetables, and raw milk, respectively. The general principle used for the development of VRB-2 agar could be applied to many other kinds of selective plating media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…Possible detrimental effects from the medium selected for enumeration of Enterobacteriuceae cannot be discounted. Trypticase soy agar (TSA) overlaid with double-strength violet red bile agar (VRB) was originally developed by Hartman et al (1975) for enumerating stressed coliforms. However, extensive testing in our laboratory (unpublished data) Although SuZmoneZZu spp.…”
Section: Resultsmentioning
confidence: 99%
“…Possible detrimental effects from the medium selected for enumeration of Enterobacteriuceae cannot be discounted. Trypticase soy agar (TSA) overlaid with double-strength violet red bile agar (VRB) was originally developed by Hartman et al (1975) for enumerating stressed coliforms. However, extensive testing in our laboratory (unpublished data) Although SuZmoneZZu spp.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that injured cells could not completely recover on a selective medium because of selective agents supplemented in the selective medium (Helander et al 2001;Wu et al 2001). A two-step overlay method was developed to recover injured bacterial cells (Hartman et al 1975;Speck et al 1975). However, the method is time-consuming and inconvenient in isolating suspicious colonies for further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli populations were determined by using lactobacilii scl&ztive agar (LB>,' BBL) containing 0.017% acetic acid and incubating the plates at 30°C for 72 hr. Mcmbcrs of the Enterobncteriaceae where enumerated in TSA overlaid with double-strength violet red bile agar (VRB, DIFCO) incubated at 37°C for 24 hr (Hartman et al, 1975). Although a spoilage level of 10' psychrotrophic bacteria/cm* and/or lo* lactobacilli/cm* had been defined on the basis of the work of Ayres (1960) and of Hanna et al (1979), respectively, sampling was discontinued earlier if offensive odors were detected when packages were opened.…”
Section: Microbiological Analysesmentioning
confidence: 99%